Innovation Capital and its Measurement - Tomasz Kijek (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Innovation capital regarded as an element of intellectual capital reflects the ability of an organization to create and commercialize the new knowledge (innovations). The aim of this study is twofold. Firstly, an attempt is made to give a concise review of innovation capital concept and its measures in selected intellectual capital – IC –models. Secondly, this paper sets out to extend the current models and introduce a new valuation method of innovation capital. Moreover, the paper provides empirical evidence about the use of the proposed method.